2021
DOI: 10.3389/fonc.2021.687208
|View full text |Cite
|
Sign up to set email alerts
|

LINC00346 Sponges miR-30c-2-3p to Promote the Development of Lung Adenocarcinoma by Targeting MYBL2 and Regulating CELL CYCLE Signaling Pathway

Abstract: BackgroundLINC00346 has recently been reported to regulate the development of several cancer types, but its biological functions and underlying mechanisms in lung adenocarcinoma (LUAD) have not been elucidated. The purpose of this study was to investigate the molecular mechanism of LINC00346 in the progression of LUAD.MethodsBioinformatics was performed to find the target lncRNA, miRNA and mRNA, and the binding relationship between the target genes was verified by dual luciferase reporter gene and RIP assays. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The upregulation of LINC00346 has been found to promote cell proliferation and inhibit cell apoptosis in many diseases. Silencing LINC00346 has been found to obviously inhibit cell proliferation and promote cell apoptosis in bladder cancer (Ye et al, 2017), lung cancer (Wang et al, 2017;Xu et al, 2021), (Jin et al, 2020;Yin et al, 2020) HCC, glioma , (Li T. et al, 2020) CRC, and breast cancer (Li et al, 2020d). Additionally, several studies have revealed that elevated LINC00346 expression enhances cell proliferation in gastric cancer (Xu et al, 2019) and pancreatic cancer (Zhang et al, 2018;Peng et al, 2019;Shi et al, 2019).…”
Section: The Role Of Linc00346 In Cellular Growthmentioning
confidence: 99%
See 4 more Smart Citations
“…The upregulation of LINC00346 has been found to promote cell proliferation and inhibit cell apoptosis in many diseases. Silencing LINC00346 has been found to obviously inhibit cell proliferation and promote cell apoptosis in bladder cancer (Ye et al, 2017), lung cancer (Wang et al, 2017;Xu et al, 2021), (Jin et al, 2020;Yin et al, 2020) HCC, glioma , (Li T. et al, 2020) CRC, and breast cancer (Li et al, 2020d). Additionally, several studies have revealed that elevated LINC00346 expression enhances cell proliferation in gastric cancer (Xu et al, 2019) and pancreatic cancer (Zhang et al, 2018;Peng et al, 2019;Shi et al, 2019).…”
Section: The Role Of Linc00346 In Cellular Growthmentioning
confidence: 99%
“…Additionally, several studies have revealed that elevated LINC00346 expression enhances cell proliferation in gastric cancer (Xu et al, 2019) and pancreatic cancer (Zhang et al, 2018;Peng et al, 2019;Shi et al, 2019). Cell cycle arrest induced by LINC00346 has been observed in bladder cancer (Ye et al, 2017), lung cancer (Wang et al, 2017;Xu et al, 2021), (Jin et al, 2020) HCC, gastric cancer (Xu et al, 2019), and pancreatic cancer (Shi et al, 2019). Knockdown of LINC00346 facilitates G1/G0 cell cycle arrest in bladder cancer (Ye et al, 2017), non-small-cell lung cancer (Wang et al, 2017;Xu et al, 2021), and (Jin et al, 2020)HCC.…”
Section: The Role Of Linc00346 In Cellular Growthmentioning
confidence: 99%
See 3 more Smart Citations